Pneumonia with Hypercapnia in a Patient with COPD and Infected Bronchiectasis: A Case Report - Muhammad Rofi Wahyu Setyadi; Gemilang Khusnurrokhman (Lombok Medical Journal, 2026)
Chronic obstructive pulmonary disease is a major global health problem with high morbidity and mortality, often complicated by acute exacerbations triggered by lower respiratory tract infections such as pneumonia. The coexistence of pneumonia, chronic obstructive pulmonary disease, and bronchiectasis creates a complex pathophysiological interaction that may lead to impaired gas exchange and hypercapnic respiratory failure. We report a case of a patient with severe chronic obstructive pulmonary disease and infected bronchiectasis presenting with pneumonia and hypercapnia. The diagnosis was established based on clinical findings, radiological imaging, and laboratory examination including arterial blood gas analysis. The patient developed type II respiratory failure characterized by carbon dioxide retention and respiratory acidosis. Management included controlled oxygen therapy, appropriate antibiotic administration, bronchodilator therapy, and supportive care. Careful oxygen titration was essential to avoid worsening hypercapnia. The patient showed clinical improvement with integrated management. This case highlights the importance of understanding the interaction between pneumonia, chronic obstructive pulmonary disease, and bronchiectasis, as well as the need for appropriate oxygen strategy in managing hypercapnic respiratory failure.